Pengaruh Pra Perlakuan Terhadap Kualitas Kunyit yang Dikeringkan dengan Menggunakan Solar Tunnel Dryer - Victoria Kristina Ananingsih; Gracia Arsanti; Robertus Probo Yulianto Nugrahedi (Institut Pertanian Bogor, 2017)
Turmeric (Curcuma domestica Val.) has many health benefits and can be used in herbal medicine as well as traditional herbal drink. Turmeric can also be used as a natural dye in food. Turmeric is very perishables in a fresh state, thus drying process is needed to extend its shelf life. An environmentally friendly drying using Solar Tunnel Dryer (STD) is one of the techniques that is interestingly developed. The purpose of this study was to determine the effect of steam blanching at different times (3, 5, and 10 minutes) and soaking using a 0.05% citric acid for 5 minutes on the physicochemical and microbiological qualities of turmeric dried by STD. Measurements were conducted to analyze water content, water activity, curcumin content, antioxidant activity, pH, water activity, color intensity, and total fungi. The results showed that steam blanching and immersion using a 0.05% citric acid for 5 minutes could reduce the drying time when compared to that of control. While 5 minutes of steam blanching with immersion in the 0.05% citric acid for 5 minutes could produce a high antioxidant activity which was 80.30 ± 0.89 (% inhibition) and it had the lowest total fungi which were 3.33 ± 5.00%